Minimally Processed Vegetables in Brazil: An Overview of Marketing, Processing, and Microbiological Aspects - Jéssica A. F. F. Finger; Isabela M. Santos; Guilherme A. Silva; Mariana C. Bernardino; Uelinton M. Pinto; Daniele F. Maffei (Foods, 2023)
The global demand for minimally processed vegetables (MPVs) has grown, driven by changes in the population’s lifestyle. MPVs are fresh vegetables that undergo several processing steps, resulting in ready-to-eat products, providing convenience for consumers and food companies. Among the processing steps, washing–disinfection plays an important role in reducing the microbial load and eliminating pathogens that may be present. However, poor hygiene practices can jeopardize the microbiological quality and safety of these products, thereby posing potential risks to consumer health. This study provides an overview of minimally processed vegetables (MPVs), with a specific focus on the Brazilian market. It includes information on the pricing of fresh vegetables and MPVs, as well as an examination of the various processing steps involved, and the microbiological aspects associated with MPVs. Data on the occurrence of hygiene indicators and pathogenic microorganisms in these products are presented. The focus of most studies has been on the detection of Escherichia coli, Salmonella spp., and Listeria monocytogenes, with prevalence rates ranging from 0.7% to 100%, 0.6% to 26.7%, and 0.2% to 33.3%, respectively. Foodborne outbreaks associated with the consumption of fresh vegetables in Brazil between 2000 and 2021 were also addressed. Although there is no information about whether these vegetables were consumed as fresh vegetables or MPVs, these data highlight the need for control measures to guarantee products with quality and safety to consumers.